2017
DOI: 10.1016/j.ejphar.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide, a glucagon-like peptide-1 analog, induce autophagy and senescence in HepG2 cells

Abstract: It has been reported that glucagon-like peptide-1 (GLP-1) agents have been associated with both the increased risk of cancer and inhibition of tumor growth and metastases. The aim of this study is to evaluate the effect of liraglutide on hepatocellular carcinoma cells - HepG2. Cytometry was used to evaluate mechanism related to decreased cell proliferation. Nuclear staining and morphometric analysis were also used to verify the process that was taking place after treatment with liraglutide, and in order to bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Autophagy is a catabolic process in which cells are subjected to stress such as hypoxia, starvation, and lack of nutrients (15). Autophagy acts as a 'double-edged sword' in tumorigenesis and development (16,17). On one hand, autophagy inhibits the occurrence and development of tumors by degrading abnormal components in cells or inducing non-apoptotic pathway death.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a catabolic process in which cells are subjected to stress such as hypoxia, starvation, and lack of nutrients (15). Autophagy acts as a 'double-edged sword' in tumorigenesis and development (16,17). On one hand, autophagy inhibits the occurrence and development of tumors by degrading abnormal components in cells or inducing non-apoptotic pathway death.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, experimental studies have shown that exendin-4 could inhibit and attenuates tumor growth (Honors and Kinzig, 2014[13]; Nomiyama et al, 2014[19]). Other studies revealed that GLP-1 analog liraglutide inhibits the growth of pancreatic cancer in animal models and hepatocellular carcinoma in HepG2 cell line (Zhao et al, 2014[29]; Krause et al, 2017[14]). These results corroborate our findings that exenatide decrease HepG2 cells viability after 48 h of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that liraglutide is capable of inducing senescence in HepG2 cells (Krause et al, 2017[14]), we have tested this effect for exenatide. Senescence and apoptosis are two mechanisms that may be responsible for the proliferation decrease, as the first is characterized by an irreversible cell cycle arrest (Childs et al, 2014[5]) and the second by a programmed cell death with nuclear fragmentation (He et al, 2009[11]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations